2010
DOI: 10.1016/j.explore.2009.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Top-Down and Bottom-Up Mechanisms in Mind-Body Medicine: Development of an Integrative Framework for Psychophysiological Research

Abstract: It has become increasingly evident that bidirectional ("top-down and bottom-up") interactions between the brain and peripheral tissues, including the cardiovascular and immune systems, contribute to both mental and physical health. Therapies directed toward addressing functional links between mind/brain and body may be particularly effective in treating the range of symptoms associated with many chronic diseases. In this paper, we describe the basic components of an integrative psychophysiological framework f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
127
0
9

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(152 citation statements)
references
References 176 publications
5
127
0
9
Order By: Relevance
“…The descriptions presented herein provide support to the hypothesis that, when beta syntonizes in the different cortical regions, it coordinates the attention and sensory-perception processes and motor functions 32,38,41,42 . Other authors have described this condition, as the manifestation of the up-down regulation of organisms 43 .…”
supporting
confidence: 77%
“…The descriptions presented herein provide support to the hypothesis that, when beta syntonizes in the different cortical regions, it coordinates the attention and sensory-perception processes and motor functions 32,38,41,42 . Other authors have described this condition, as the manifestation of the up-down regulation of organisms 43 .…”
supporting
confidence: 77%
“…These two methods are both mind and body therapies of bottom-up mechanism, initiated by stimulation of peripheral receptors as somato-, viscero-or chemosensory receptors that influence central neural processing and mental activities from the periphery to the brain system and cerebral cortex. (8) To compare them to others but of top-down mechanism (initiated via mental processing at the level of cerebral cortex), two more arms are implemented with, respectively, Hp and Mt. A non-intervention resting arm is the control group.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…(19) ) In the Hp domain, which is out of the field of this study, literature about the therapeutic mechanisms on anxiety is also available. (8) Previous studies have already been carried out on the management of psychosocial stress with CAMs, but few of them have been with people in reasonably good health. A study reviewing intervention trials on maternal anxiety in pregnancy (46) measured by the STAI showed that scores appear amenable to change after a single session of CAMs interventions, but neither Fs nor Rf were assessed.…”
Section: The Clinical Effects Of the Different Conditions Is An Impormentioning
confidence: 99%
“…In instances where continued physiological hyperarousal and altered stress hormone secretion afect the ongoing evaluation of sensory stimuli, it has been shown that botom-up neurophysiological interventions more efectively address "the repetitive, unbidden, physical sensations, movement inhibitions, and somatosensory intrusions of unresolved trauma, than do top-down interventions" [54]. In such cases, a therapeutic model that efectively integrates both top-down (where the cranial brain sends messages to the body) and botom-up interventions (embodied sensory receptors communicate with cranial based sensory receptors) best serves recovery [55].…”
Section: Understanding the Trauma Phenomenonmentioning
confidence: 99%